Highly enhanced dielectric strength and energy storage density in hydantoin@BaTiO3–P(VDF-HFP) composites with a sandwich-structure1. Issue 65 (16th July 2015) - Luo, Hang; Zhang, Dou; Wang, Lu; Chen, Chao; Zhou, Jing; Zhou, Kechao
<x xml:space="preserve">Abstract</x> The dielectric strength and discharged energy density are largely enhanced in the sandwich-structured hydantoin@BaTiO3–P(VDF-HFP) composites.